Fatal course of ABO hemolytic disease associated with hydrops in a twin pregnancy - Tiker, Filiz; Gürakan, Berkan; Tarcan, Aylin; Ozbek, Namik (The Turkish Journal of Pediatrics, 2006)
Hydrops fetalis associated with ABO incompatibility is an extremely rare condition. We report twin infants both afflicted with significant ABO hemolytic disease but showing different degrees of clinical severity, in which fatal hydrops developed in one of the twins. Hemolysis due to ABO incompatibility is usually difficult to diagnose. All causes of non-immune hydrops should be ruled out in order to identify hydrops due to ABO incompatibility.